Joint universality of periodic zeta-functions with multiplicative coefficients - Laurinčikas, Antanas; Tekorė, Monika (Nonlinear Analysis: Modelling and Control, 2020)
The periodic zeta-function is defined by the ordinary Dirichlet series with periodic coefficients. In the paper, joint universality theorems on the approximation of a collection of analytic functions by nonlinear shifts of periodic zeta-functions with multiplicative coefficients are obtained. These theorems do not use any independence hypotheses on the coefficients of zeta-functions.
Keywords: joint universality; periodic zeta-function; space of analytic functions; weak convergence